'Potency is important for a real man': Affective Readings of Shame and Performance Anxiety in Spam Selling Viagra and other Sexuopharmaceuticals. (April 2021) - Jensen, Mie Birk; Jänicke, Stefan
Abstract : Viagra is a popular topic in spam, but contrary to Pfizer's official marketing of Viagra, little attention has been directed at how the content of spam plays into gendered discourse on masculinity and men's sexual performances. This is not surprising, if we consider how spam is mostly treated as a nuisance to digital infrastructures. Yet, studies have demonstrated how spammers build on, reflect and transmit gender ideologies (e.g. Mullany 2004 ; Paasonen 2009 ; Yu 2014 ). In the present paper, we contribute insights to the existing studies on Viagra and spam, as we examine how spammers promote Viagra and other sexuopharmaceuticals. Taking our point of departure in an online spam archive (Guenter 2010 ), we combine qualitative and quantitative methods to analyse the textual content of spam emails. Using TagSpheres models, we have produced an overview of the most frequent and relevant terms in spam which we further subject to a qualitative analysis. Drawing on Sara Ahmed (2004), we engage in an affective reading of selected spam emails, generated by randomised samples. In the analysis, we argue that spammers attempt to move possible consumers away from official and legal sale methods by emphasising shame and anxiety related to procuring Viagra and other sexuopharmaceuticals. While shame moves the consumer away from legal sale methods, anxiety is invoked to encourage the possible consumer to envision a hypermasculine future, in which virility is everlasting. We further discuss our findings in relation to masculinity, arguing that spammers capitalise on existing communication- and pharmaceutical technologies, whilst taking gendered discourse in advertising to their 'functional extremes' (Brunton 2019 : xiv).